Customary Sanctions in the Kitab Simbur Cahaya Ratu Sinuhun Study of Dark Pregnant Women in Indigenous Communities Inland South Sumatra - Farida, Annikmah; Setiawan, Agus (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
This article is to analyse the practice of customary sanctions for women who are dark pregnant in the Kitab Simbur Cahaya as practised by the Inland Communities of South Sumatra. Then analyse the reasons why the people of the interior of South Sumatra still apply customary sanctions for women who are dark pregnant. This article is qualitative. The research was conducted field research supported by library research. The object of research was conducted in the inland communities of South Sumatra. The approach used in this research is a case approach. Data collection techniques by means of observation, interviews and documentation. The results of the discussion are, the form of customary sanctions for dark bunting women, namely fines and mbasuh dusun sanctions. The implementation of the mbasuh dusun sanction is by slaughtering livestock in the form of male goats whose bellies are striped with white fur. The blood of the goat is used to wash the hands and feet of the adulterer. Sanctions for adultery perpetrators in the form of mbasuh dusun are customary sanctions that are complaints. Regarding the status of illegitimate pregnant women victims of rape, the Kitab Simbur Cahaya does not explain in detail, but in fact in the inland community, illegitimate pregnant women victims of rape are still given sanctions. The reason why the people in the interior of South Sumatra apply customary sanctions for women who are illegally pregnant is as a preventive measure, as an effort to educate women, while the mbasuh dusun sanction is to avoid all kinds of calamities that will occur in the village.